Plasma leptin levels are lower in females, but not males, with ketamine use disorder - Huang, Ming-Chyi; Chiang, Li-Jung; Chien, Wan-Hsi; Liu, Tung-Hsia; Chen, Chun-Hsin; Liu, Yu-Li (The American journal of drug and alcohol abuse, 2024)
Ketamine has emerged as a prominent substance of misuse. Leptin, an adipocyte-derived polypeptide hormone, has been implicated in the development of addiction. Sex-specific changes in leptin levels have been demonstrated following acute ketamine administration; the persistence of long-term ketamine use on leptin levels is uncertain. To assess the sex-difference of leptin levels, and their persistence, in individuals with ketamine use disorder (KUD) compared to healthy controls. Plasma leptin levels were measured in 62 healthy controls (37 males, 25 females) and 68 participants with KUD (50 males, 18 females) on the first day (baseline) and after 1 and 2 weeks of abstinence. As leptin levels are affected by body mass index (BMI), BMI-adjusted leptin (leptin/BMI ratio) was also examined. Mixed model for repeated measures was used to examine changes after ketamine abstinence. Compared to same-sex controls, female, but not male, participants with KUD demonstrated lower leptin levels and leptin/BMI ratio at baseline, week 1, and week 2 (leptin levels: = .001, 0.006 and 0.032, respectively; leptin/BMI ratio: = .004, 0.022, and 0.09, respectively). Repeated measures showed that leptin levels and the leptin/BMI ratio increased after 2 weeks of abstinence in male participants with KUD ( = .002 and 0.011, respectively), but females did not show such an increase ( > .05). Sex-specific differences were observed in leptin levels and the leptin/BMI ratio in individuals with KUD compared to controls. Lower leptin levels in females with KUD persisted after 2 weeks of abstinence.